NODULATION, SEED YIELD AND ITS RELATED TRAITS RESPONSE OF COMMON BEAN (PHASEOLUS VULGARIS L.) CULTIVARS TO NPS FERTILIZER UNDER ACIDIC SOIL - Endrias Chinasho,; Maguje Masa, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to evaluate the response of common bean cultivars to NPS fertilizer. Results revealed that the main effect of NPS rates, and cultivars highly significantly affected 50% days to flowering, number of primary branches per plant, pods per plant, hundred seeds weight, above-ground dry matter biomass, and grain yield. Nasir cv. provided highest  for all the studie parameters, among NPS rate, 100 kg ha-1 recorded the highest results for the  50% days to flowering, the number of primary branches per plant, pods per plant, hundred seeds weight, above-ground dry matter biomass, and seeds yield. The interaction effects of NPS rate and cultivars highly significantly influenced days to 90% physiological maturity, plant height, total and effective nodule number, and the number of seeds per pod. Thus, cultivar Nasir interaction with 100 kg ha-1 NPS rate resulted in higher total and effective nodule number, seeds per pod, and the less for plant height which was recorded highest result for Red Wolaita with 100 kg ha-1 NPS rate. This study was revealed that cultivar Nasir with the optimum amount of NPS fertilizer application, the common bean can produce a more effective nodule that is capable of fixing atmospheric nitrogen for plant nourishment under acidic soil..It can be  concluded as the combined use of 100 kg ha-1 NPS with cultivar Nasir results in higher grain yield and soil fertility improvement through nitrogen fixation for succeeding crops.